2021
DOI: 10.1101/2021.06.07.447373
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evidence for a vocal signature in the rat and its reinforcing effects

Abstract: While the term 'language' is used for human and non-human primates, 'vocal communication' is rather used for rodents or other species. The main difference is that there is, to date, no evidence for a vocal signature in the well-known 50- and 22-kHz ultrasonic vocalizations (USV) emitted by rats. Here, we show that rats can recognize the identity of the USV emitter since they self-administer preferentially playback of 50-kHz USV emitted by a stranger rat over those emitted by their cage-mate. In a second experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 65 publications
(104 reference statements)
0
1
0
Order By: Relevance
“…A recent study demonstrated that rats distinguish a USV emitter, and they self-administer preferentially playback of 50-kHz USVs emitted by a stranger rat over those emitted by their cage mate. 60 We used playback footage of a rat that was a stranger to the observers, whereas the live demonstrators were familiar to the observers. Using live demonstration of a stranger rat, therefore, might have been a more rewarding stimulus to the observer rats.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study demonstrated that rats distinguish a USV emitter, and they self-administer preferentially playback of 50-kHz USVs emitted by a stranger rat over those emitted by their cage mate. 60 We used playback footage of a rat that was a stranger to the observers, whereas the live demonstrators were familiar to the observers. Using live demonstration of a stranger rat, therefore, might have been a more rewarding stimulus to the observer rats.…”
Section: Discussionmentioning
confidence: 99%